KENDALA PEMBELAJARAN DARING MAHASISWA PENDIDIKAN GEOGRAFI FIS UNP ANGKATAN 2017 - Novita Agustina Agustina; Nofrion Nofrion (JURNAL BUANA, 2021)
This study aims to describe online learning constraints faced by 2017 geography education students in the Covid-19 vigilance period. This type of research is a qualitative research with a phenomenological approach. The subjects of this study were 2017 geography education students. Data collection techniques used were interviews, and documentation. Data analysis techniques using the interactive model of Miles and Huberman consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that Geography education students 2017 experience online learning constraints in the form of (1) geographical constraints, students live in areas that have a bad internet network, (2) economic constraints, students have financial difficulties to buy internet data packages, (3) learning facilities, students do not have enough memory cards to download online learning applications, (4) constraints to understanding the material, students have difficulty understanding the subject matter in online learning asynchronous type, (5) constraints on technology use, poor internet network and (6) the task load constraints, students do not have enough time to do a lot of assignments and a bad internet network so students have difficulty sending assignments to their lecturer.